rs3798577 polymorphism located in a putative miRNAs target site of estrogen receptor 1 reduced breast cancer risk in an Iranian population - Reisi Dehkordi, Nafiseh; Parsafar, Soha; Ghaedi, Kamran; Peymani, Maryam (European Journal of Oncology and Environmental Health, 2018)
Purpose: In the current case-control study, the possible association between rs3798577, a microRNA-related SNP located on ESR1 3’-untranslated regions (3’-UTR), and breast cancer was evaluated in Iranian women for the first time. Materials and Methods: 126 breast cancer patients and 141 hospital healthy controls were enrolled in this study. Genotyping of the selected SNP in ESR1 was disclosed using the allele-specific primer polymerase chain reaction (ASP-PCR) assay. Odds ratio, 95% confidence interval, and p value were calculated to examine the association between SNP and breast cancer related clinical features. In addition, an in silico prediction was performed to identify potential functionality of the SNP within miRNA binding sites in the 3’-UTR of ESR1. Results: The T allele carriers of the SNP had significantly inverse association with BC incidence (T/T and C/T vs C/C; OR, 0.50; 95% C.I., 0.27-0.92; P value, 0.025). In addition, T allele carriers conferring decreased risk of metastasis, ER/PR negativity, HER2 positivity, and stage IV incidence and also increased risk of BC death and grade III incidences but these results did not reach statistical significance. Bioinformatically, rs3798577 is located on ESR1 3’-UTR within the potential target sequence of miR-1278 and miR-125b-2-3p. Hence, the T allele may increase miRNA-mRNA binding strength. Conclusion: The results showed that the ESR1 rs3798577 T allele significantly reduced breast cancer risk, in agreement with bioinformatical results. The association between rs3798577 genotypes and breast cancer has been reported contradictorily in different studies. Furthermore, the bioinformatical results need to verify. Therefore, further studies with large sample size and functional assessment are strongly suggested.